Should Slovenia transform the accounting in public sector? - Jovanović, Tatjana (Mednarodna revija za javno upravo, 2015)
Even before, but especially in time of financial and economic crisis, countries are facing a challenge to improve the information served by public accounting for the state budgeting purpose, most often by reforming accounting principle from cash flow into accrual. The majority of literature impose the opinion that the accrual accounting facilitates more transparent and complete review of the business activities and property of the users of public funds than cash principle does and that additionally provides more transparent budgeting. The article evaluates the pros and cons of the public sector accounting transformation in Slovenia using arguments for a simple SWOT analysis in experience of other countries, presented in the literature.
Keywords: javni sektor; proračun; računovodske reforme; računovodstvo; Slovenija